2014
DOI: 10.1155/2014/523210
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Substituents of the Phenylmethylsulfamide Moiety Can Be Used for the Development of New Selective Carbonic Anhydrase Inhibitors

Abstract: A new series of compounds containing a sulfamide moiety as zinc-binding group (ZBG) has been synthesized and tested for determining inhibitory properties against four human carbonic anhydrase (hCA) isoforms, namely, CAs I, II, IX, and XII. The X-ray structure of the cytosolic dominant isoform hCA II in complex with the best inhibitor of the series has also been determined providing further insights into sulfamide binding mechanism and confirming that such zinc-binding group, if opportunely derivatized, can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…To understand if the different position assumed by N2 and O3 atoms in the enzyme active site was associated to a peculiarity of the two complexes under investigation, or to a more general behaviour of sulphamate and sulphamide derivatives, a comparative analysis of all hCA II/sulphamate and hCA II/sulphamide structures available in the PDB was undertaken 25,26,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][67][68][69][70][71] . Surprisingly, the analysis of all these structures revealed that, independently of the nature of the moiety attached to the ZBG, the distance between the Thr200OG1 atom and the sulphamide nitrogen N2 in hCA II/sulphamide complexes was generally shorter than the corresponding distance between the sulphamate oxygen O3 and the same enzyme atom in hCA II/sulphamate complexes (see Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…To understand if the different position assumed by N2 and O3 atoms in the enzyme active site was associated to a peculiarity of the two complexes under investigation, or to a more general behaviour of sulphamate and sulphamide derivatives, a comparative analysis of all hCA II/sulphamate and hCA II/sulphamide structures available in the PDB was undertaken 25,26,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][67][68][69][70][71] . Surprisingly, the analysis of all these structures revealed that, independently of the nature of the moiety attached to the ZBG, the distance between the Thr200OG1 atom and the sulphamide nitrogen N2 in hCA II/sulphamide complexes was generally shorter than the corresponding distance between the sulphamate oxygen O3 and the same enzyme atom in hCA II/sulphamate complexes (see Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that some derivatives characterized by different substituents including CH 3 , CF 3 , CN, F, Cl, Br, NO 2 , OCH 3 and Ph at the ortho-, meta-and parapositions of the benzylic or benzoylic portion in their skeleton have inhibition profiles against CA isoenzymes 99 . All the synthesized compounds were tested to evaluate their inhibitory activity towards the slower cytosolic isoform (hCA I), the more rapid cytosolic isoenzyme (hCA II) and AChE/BChE enzymes.…”
Section: Biochemical Resultsmentioning
confidence: 99%
“…In addition to this, sites of interaction of the compound 13c with human carbonic anhydrase I (hCA I), human carbonic anhydrase II (hCA II), human acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and α‐glycosidase enzymes were also determined. Crystal structures in complex with inhibitor (PDB ID: 2FW4 for hCA I, 4PQ7 for hCA II, 4M0E for AChE, 5LKR for BChE, and 3A4A for α‐glycosidase) were prepared using protein preparation wizard of Maestro . Three‐dimensional structure of compound 13c was constructed using the LigPrep module of Maestro .…”
Section: Methodsmentioning
confidence: 99%